Road injuries among older people in a tertiary care hospital in Sri Lanka - a comparative analysis - Varuni Tennakoon; Roshini Peiris-John; Rajitha Wickremasinghe; Bridget Kool; Shanthi Ameratunga (College of Community Physicians of Sri Lanka, 2020)
Introduction: With escalating incidence of road traffic crashes (RTCs), related injuries and deaths in Sri Lanka, understanding its burden on vulnerable road users such as older people and people with disability have important implications for traffic injury prevention and transport policy planning.   Objectives: To determine crash characteristics and patterns of injuries sustained by victims of RTCs admitted to a tertiary-care hospital and investigate if these differ for older people   Methods: Recorded data of all victims of RTCs admitted to the Colombo South Teaching Hospital from 1 January to 31 March 2017 were systematically extracted and analysed.   Results: Of the 573 victims, 70 (12.2%) were older people aged 60 years and above. Pedestrians (46%) were the most common road user type injured among older people. In contrast, among younger victims, the motorcyclists dominated (54%). Older people were involved in RTC between 9.01 am and 12.00 noon more often than those who were younger (22% vs. 9.5%), and had significantly higher incidence of severe head injuries (13% vs. 3%), fractures (54% vs. 40%) and deaths (10% vs. 2%), and referrals to rehabilitation services at discharge (60% vs. 39%).   Conclusions: Older road crash victims are at higher risk of head injuries, fractures, and deaths than younger people. Given the lack of documented data, the influence of pre-existing disability on road injury outcomes could not be investigated. Future injury surveillance, intervention and evaluative efforts should explicitly consider the needs of these vulnerable road users.